Effects of elevated CO2 concentration and temperature on growth and production of Oryza sativa L. cv. Ilmi, one of the main rice varieties in Korea - Eung-Pill Lee; Jae-Hoon Park; Rae-Ha Jang; Young-Han You (Journal of Ecology and Environment)
This research was conducted to examine the changes in growth and production of Oryza sativa L. cv. Ilmi, which was developed to cultivate high yielding rice variety in the Southern plains of Korea. The seedlings of the rice were cultivated from May to October in 2012 under three different conditions: control, AC-AT, ambient CO2 + ambient temperature; AC-ET, ambient CO2 + elevated temperature; EC-ET, elevated CO2 + elevated temperature. The aboveground biomass, belowground biomass, the total biomass of the rice, and panicle weight per individual were the heaviest in the EC-ET. But, the number of grains per panicle and the weight of one grain was higher at the condition of AC-ET and EC-ET than that of AC-AT. The number of tiller was higher at the condition of AC-AT and AC-ET than that of EC-ET. However, there was no significant difference in the number of panicles per individual and the ripened grain rate among the control and global warming treatments. Crop yield was the highest in the EC-ET. This result means that the global warming condition should be considered in the selection of suitable paddy field for the limibyeo in the future.